2022
DOI: 10.1111/epi.17320
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of machine learning models for prediction of seizure outcome after pediatric epilepsy surgery

Abstract: Objective: There is substantial variability in reported seizure outcome following pediatric epilepsy surgery, and lack of individualized predictive tools that could evaluate the probability of seizure freedom postsurgery. The aim of this study was to develop and validate a supervised machine learning (ML) model for predicting seizure freedom after pediatric epilepsy surgery.Methods: This is a multicenter retrospective study of children who underwent epilepsy surgery at five pediatric epilepsy centers in North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(40 citation statements)
references
References 43 publications
1
38
1
Order By: Relevance
“…Machine learning in clinical research is placing an increasing emphasis on model generalizability, where the highest level of evidence is achieved from applying models externally -to new centers. When we tested the model by Yossofzai et al 23 on our data, we found that it did not generalize well. This may at first glance seem surprising, as there is a striking similarity between our cohort and the cohort of Yossofzai et al 23 -not only in terms of sample size, but also in terms of patient characteristics and variables found to be predictive of outcome.…”
Section: In Pursuit Of (Geographical) Model Generalizabilitymentioning
confidence: 73%
See 4 more Smart Citations
“…Machine learning in clinical research is placing an increasing emphasis on model generalizability, where the highest level of evidence is achieved from applying models externally -to new centers. When we tested the model by Yossofzai et al 23 on our data, we found that it did not generalize well. This may at first glance seem surprising, as there is a striking similarity between our cohort and the cohort of Yossofzai et al 23 -not only in terms of sample size, but also in terms of patient characteristics and variables found to be predictive of outcome.…”
Section: In Pursuit Of (Geographical) Model Generalizabilitymentioning
confidence: 73%
“…When we applied the XGBoost model developed by Yossofzai et al 23 to our data, it achieved an accuracy of 63% (95% CI=59-67%) and an AUC of 0.62.…”
Section: External Xgboost Modelmentioning
confidence: 93%
See 3 more Smart Citations